Aromaterapi Lavender Sebagai Terapi Terapi Non-Farmakologis Untuk Hipertensi Lansia: Studi Deskriptif - Retnowati, Lucia; Syifa Azahra Irawan; Agus Setyo Utomo (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Hypertension in the elderly is a chronic health issue that requires continuous care and holistic management strategies. One emerging non-pharmacological intervention is aromatherapy, particularly with lavender essential oil, known for its calming and relaxation effects. This study aimed to explore the effectiveness of lavender aromatherapy as a complementary approach in managing blood pressure among elderly individuals with hypertension. A descriptive study design was employed, utilizing both qualitative and quantitative approaches. Data were collected through direct observation of blood pressure and the accuracy of self-administered therapy, alongside semi-structured interviews conducted over four consecutive days. The findings indicated a gradual decrease in blood pressure following lavender aromatherapy sessions, accompanied by improved accuracy in therapy implementation and enhanced physical and emotional well-being. Participants reported subjective improvements, including reduced physical discomfort, increased relaxation, and better sleep quality. In contrast to previous studies that primarily focused on short-term physiological effects or clinical settings, this study emphasizes the self-administered application of lavender aromatherapy among the elderly in real-life contexts. By integrating both physiological and subjective perspectives, this research provides a more holistic understanding of aromatherapy’s role in hypertension management and demonstrates its feasibility within community-based primary healthcare. The study contributes to the growing body of knowledge on complementary health interventions and suggests the need for further experimental studies with control groups and larger sample sizes to enhance the generalizability of findings